Addressing the discrepancy of finding the equilibrium melting point of silicon using molecular dynamics simulations. (30th June 2017) - Chavoshi, Saeed Zare; Xu, Shuozhi; Goel, Saurav
Abstract : We performed molecular dynamics simulations to study the equilibrium melting point of silicon using (i) the solid–liquid coexistence method and (ii) the Gibbs free energy technique, and compared our novel results with the previously published results obtained from the Monte Carlo (MC) void-nucleated melting method based on the Tersoff-ARK interatomic potential (Agrawal et al. Phys. Rev. B 72, 125206. (doi:10.1103/PhysRevB.72.125206 )). Considerable discrepancy was observed (approx. 20%) between the former two methods and the MC void-nucleated melting result, leading us to question the applicability of the empirical MC void-nucleated melting method to study a wide range of atomic and molecular systems. A wider impact of the study is that it highlights the bottleneck of the Tersoff-ARK potential in correctly estimating the melting point of silicon.